The Role of the Mentor in the First Year of Teaching - Kadyrova, Samal (NUGSE Research in Education, 2(1), 2017)
This article explores the effectiveness of mentorship relationships in addressing first year teachers’ challenges at the beginning of their career at one of the Kazakhstani private schools. The study examines the concept of mentoring, the challenges beginning teachers face, the benefits of them, and the experiences of mentorship relationships worldwide and on the territory of Kazakhstan. One-on-one interview has been chosen as the most appropriate research strategy because it helped the researcher to develop a detailed understanding of the mentorship relationship experiences within the mentoring program at school. The results of this study have shown that all participants experience various difficulties in the inaugural period of their career. Even though the existing mentoring programs are the way to enhancement; they have definitely a positive effect on first-year teachers’ professional development.
Keywords: First-year teachers; mentorship; teacher relationships; professional development